HIV: Prevention of mother-to-child transmission basic knowledge of HIV and PMTCT of women in Indonesia - Astri Mutiar; Agus Hendra; Nunung Nurhayati (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2022)
Background: The HIV-infected population is experiencing a shift in trends that lead to public health problems. This causes an increase in the incidence of HIV among housewives or women. Knowledge of mother-to-child transmission in women has an important aspect in the success of prevention practices. Having limited knowledge may cause women to avoid screening and testing for HIV.Purpose: To identify the HIV prevention of mother-to-child transmission and basic knowledge of HIV and PMTCT among women in Indonesia.Method: A cross-sectional study design was conducted with a sample size of 137 women. The convenience sampling method was used to recruit the sample between June to September 2020. Demographic characteristics and knowledge of the Indonesian version of PMTCT from V.N ADDO were used for data collection. Descriptive analysis and cross tabs for statistical analysis.Results: The majority of respondents don’t know their own HIV status (93.4%). Most respondents answered that HIV is a sexually transmitted infection disease (94.1%), having no cure (46.3%), and can be prevented by being faithful to partner (93.4%), selected before birth is the time of transmission infection from mother to baby (76.5%), and giving medication to pregnant women is the way to prevent transmission (43.3%). On the other side, most of the respondent doesn’t know time from infection to appearance of symptoms (83.8%) and in terms of MTCT knowledge, here are still 36.8 women don’t know how to prevent PMTCT.Conclusion: Improving comprehensive information dissemination from healthcare professionals by using mass media is needed to improve knowledge and service uptake to succeed in the PMTCT program.